Localized biphasic type malignant mesothelioma arising in the peritoneum: Report of a case - Kohno, Mikihiro (Thorac Cancer, 2014)
This report describes a rare case of localized malignant biphasic (mixed epithelioid and sarcomatoid) mesothelioma arising in the peritoneum. A 69-year-old male with a history of asbestos exposure, complaining of a painful mass in the left chest wall, was found via computed tomography (CT) to have a tumor in the left peritoneum. The resected tumor was histologically and immunohistochemically consistent with a malignant mesothelioma with mixed epithelioid and sarcomatoid type and no distant metastasis. The diagnosis of localized malignant biphasic mesothelioma arising in the peritoneum was appropriate because there was no evidence of any other primary tumor.